PERANCANGAN MESIN PEMANASAN INDUKSI UNTUK STEEL FORGING DENGAN TEMPERATURE CONTROLLER: Indonesia - Rachmat, Asep; nur hidayatulloh, jajang (J-ENSITEC, 2023)
Induction heating is a heating system that uses magnetic field induction generated from high frequencies. This process occurs with the presence of eddy currents or central currents whose circular direction surrounds the magnetic field that penetrates the object. Induction heating uses the principle of heating due to eddy currents produced by magnetic flux originating from coil windings that are electrified by alternating current (AC). Designing an induction heating machine, for the forging process which has the advantage of heating accuracy and a heating temperature that can be adjusted to reach a temperature of 800 ºC with a power of 1300 KW. Induction Heating Machine Design consists of Design Making which includes the frame, required voltage, circuit breaker circuit, power produced, Material Selection, Component Selection and Assembly. Induction heating machines use two power supplies, a copper coil